Recommendations for outpatient parenteral antimicrobial therapy in Brazil - Oliveira,Priscila R. (2017)
ABSTRACT A panel of national experts was convened by the Brazilian Infectious Diseases Society in order to determine the recommendations for outpatient parenteral antimicrobial therapy (OPAT) in Brazil. The following aspects are covered in the document: organization of OPAT programs; patient evaluation and eligibility criteria, including clinical and sociocultural factors; diagnosis of eligibility; venous access and antimicrobial infusion devices; protocols for antimicrobial use and monitoring and cost-effectiveness.